Promoting Peer Interactions To Develop Social Skill - Apriliaswati, Rahayu (UNIVERSITAS TANJUNGPURA, 2011)
One of the goals of elementary education is to provide students with basic skills to students to develop their lives as individuals, members of the community, citizens, and members of well being as well as preparing them for further education. Using a case study of action research, this qualitative study focused on promoting peer interactions to develop positive civil discourse of students. Results were that students performed all indicators of social interaction competence. Students were able to perform their attentive listening by maintaining direct eye contact, standing still, and taking turn at talking. They also were able to contribute ideas which focused on the topic being discussed. The students could frequently ask referensial and essential questions relevant to the topic. Students also could make their arguments respectfully and reach their compromise easily and in civil manner. The findings of this research verify that peer interactions in the classroom are not disruptive. If the teacher manages the interactions effectively, peer interactions in the classroom support not only literacy learning but also social skill development such as respect, tolerance and cooperative as the foundation of living in democratic society.